RESEARCH OF DIFFERENCES BETWEEN OPERATING CASH AND CASH ON BANK ACCOUNT IN SELECTED PHARMACEUTICAL COMPANIES IN THE REPUBLIC OF SERBIA - Popović Stefanović, Jelena (International Journal of Economic Practice and Policy, 2022)
This research analyzes EBITDA as operating cash and an indicator of the company's earning capacity and cash on account at the end of the business year. The study underlines the difference between EBITDA as operative cash and cash that is really on the account at the end of the business year and shows whether there is an interdependence between these two coefficients. The paper accepts the null hypothesis and rejects the alternative, so it can be concluded that there are differences between operating cash (EBITDA) and cash on the bank account at the end of the business year.The difference between a company's annual earnings and what is on the account at the end of the business year is clarified. Some of the relevant questions are: Are EBITDA and cash on bank account the same? What are the differences between these two concepts? As the answer to the first question is negative, internal and external stakeholders cannot save time in calculating the EBITDA ratio by observing only the account balance at the end of the business year. The second question was used for research for a more detailed explanation of these two concepts.
Keywords: EBITDA; cash; account; company; stakeholders; business year; calculating